Chronic alcohol intoxication and liver diseases - A. I. Khazanov; S. V. Plyusnin; S. A. Belyakin; A. P. Vasiliev; A. N. Bobrov; A. I. Pavlov; S. G. Pehktashev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To determine pattern of changes of prevalence, and outcomes of alcoholinduced liver disease at inpatients and relation of these changes to consumption of alcohol in the country at retrospective investigation.Materials and methods. For the years 1946–2005 2621 patient with liver cirrhosis (LC) were investigated, including 1362 patients with alcohol-induced liver cirrhosis (ALC) and acute alcoholic hepatitis (AAH) on a background of LC. The study also included 115 patients with AAH on a background of alcoholic steatohepatitis and 232 patients with hepatocellular carcinoma (HCC). Comparison group included 517 patients with acute viral hepatitis (AVH).Results. Sixfold increase of alcohol consumption by the USSR-Russia population for 1946–2006 resulted in 8,5 times increase of number of ALC patients for specified interim, whereas the total number of patients with LC increased 4,1 times. During the years of limited sale of alcohol (1985–1989) the LC-related mortality decreased 2,6 times in comparison to previous five years. In 1996–2005 the number patients, died of alcohol-induced cirrhoses considerably exceeded this score for viral cirrhoses (104 and 36 respectively). Nevertheless, due to improvement of treatment the mortality at alcohol-induced cirrhoses in 2001–2005 decreased by 18%, but at HBV LC and especially at HCV LC these scores decreased in greater degree. In 1993- 2000 517 AVH patients were observed, of them lethal outcome developed at 11 (2,1%), of 127 AAH patients 24 died (18,9%). From 1992 to 2005 the proportion of alcohol-associated HCC increased by 58%. The brief comparative characteristic of main clinical and morphological nosological forms of alcohol-induced liver disease is presented. Facts on incompetence of myths, justifying alcohol abuse, are put forward.Conclusion. Dominating growth of ALC is marked. In the years of limited sale of alcohol the number of LC with lethal outcome dramatically decreased. At the last decade the number of ALC patients with lethal outcome apparently exceeded similar figure for viral LC. Mortality rate for AAH in comparison to AVH patients was much higher.